The Relation Between Social Support, Coping Skill And Concurrent Drug Use Among Methadone Maintenance Treatment Clients At Kelantan - Ahmad Fatihi Bin Makhtar
Introduction: Concurrent drug use among MMT clients has raised serious concerns and undermined the effectiveness of MMT program. Enhancing and maintaining the client’s good social support and coping skill may have potential to counter this problem. To clarify this issue, we comprehensively explored the relation between social support, coping skills and concurrent drug use among MMT clients at Kelantan. Method: Face-to-face surveys were conducted with 312 clients randomly recruited from 28 MMT government facilities throughout each district at Kelantan. The Multidimensional Scale of Perceived Social Support (MSPSS) was used to assess client’s perceived social support, the Brief COPE questionnaire was used to assess coping strategies and concurrent heroin use was measured based on self-report of concurrent drugs use during the past 7, 30 and 90 days. Result: Among the 312 participants, 48.4% self-reported to have continued illicit drug use within 30 days with used opiate 49.7% and followed by Amphetamines (Pil Kuda) with 39%. Among them, 42.9% reported still practiced injected opiate drugs and 10.2% reported injected amphetamine (Pil Kuda). Based on our analysis, it was found that having higher levels of perceived social support (OR=0.98, 95% CI .96,.990) and the implementation of adaptive coping strategies (OR=0.92, 95% CI .87-.97) was associated with lower likelihood of concurrent drug use. On the other hand, the use of maladaptive coping strategies (OR=1.19, 95% CI 1.12,1.26) such as self-blame, humour, substance use and behavioural disengagement and unsatisfied with dose (OR=2.19, 95% CI 1.07,4.48) was associated with increased likelihood of concurrent drug use. Conclusion: Adaptive coping strategies synergized with higher levels of perceived social support may serve a key psychosocial predictor in successful recovery process among MMT clients at Kelantan.